PRODUCTION OF POLYUNSATURATED FATTY ACIDS BY MICROORGANISMS ISOLATED IN THE BRAZILIAN PAMPA BIOME - Tonato,Denise (2018)
Abstract One hundred fifty fungal strains were isolated from the Pampa biome for production of polyunsaturated fatty acids (PUFA). Microbial oil was produced by submerged cultivation at 120 rpm, 28 ºC for 7 days. Seven strains showed the best results for lipids accumulation, and they were selected in order to evaluate the influence of the temperature (15 and 28 ºC) on the lipid production and profile. The fungus Nigrospora sp. produced the highest lipid level: at 28 ºC were produced 11.28% of lipids and 51.94% of PUFA and at 15 ºC were produced 6.02% of lipids and 42.39% of PUFA. Plackett Burman design was performed to investigate the main effects of the temperature (15-25 ºC), pH (4.0-6.0), agitation (120-200 rpm), corn steep liquor (5-15% (v/v)) and sucrose concentrations (60-180 g L-1). The highest PUFA production (55.75%) was observed at the lowest temperatures (15 ºC), whereas the maximum lipid production was 5.54% at 25 ºC.